Analysis of Deddy Corbuzier's Podcast on Islamic Moral Values - Rosyadi, M. Hafidz Ilham; Mufida, Khusnul; Muttaqin, Muhammad Imamul (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
Deddy Corbuzier's podcast has become one of the popular media to discuss various issues, including Islamic moral values. This study aims to analyze the moral deviations discussed by guest stars on Deddy Corbuzier's podcast, including adultery, drunkenness, corruption/theft, and drugs.The research method used is qualitative content analysis with a descriptive approach. The research data was obtained from transcripts of Deddy Corbuzier's podcasts that are relevant to the research topic. The results of the study show that Deddy Corbuzier's podcast discusses various moral deviations that are contrary to Islamic values.The discussion about adultery focuses on the dangers of adultery and the importance of maintaining self-esteem. The discussion about drunkenness emphasizes the negative effects of alcohol and the importance of maintaining health. The discussion about corruption/theft highlights the dangers of corruption and the importance of honesty. The discussion about drugs emphasizes the dangers of drug abuse and the importance of rehabilitation. Deddy Corbuzier's podcast can be an educational medium to raise public awareness about Islamic moral values. This podcast can help masyarakat understand the dangers of moral deviations and the importance of protecting themselves from reprehensible acts.